(untitled) (ARQUISUR Revista, 2022)
This article describes a joint research partnership between researchers in Switzerland and Brazil to develop innovative experi-ences on Textile Reinforced Concrete (TRC) upgrading the works with Argamassa Armada built by the Brazilian architect João Filgueiras Lima, Lelé. Since 2016, this research is developed exchanging knowledge and developing new pedagogical approach-es by means of construction workshops and hands-on student activities. As a result, the twentieth century prefab technologies are updated considering a sustainable and contemporary framework, materialized by a TRC Prototype Pavilion built in Fribourg, Switzerland.